Effect of Wheatgrass Juice on Nutritional Quality of Apple, Carrot, Beet, Orange and Lemon Juice - Sanja Grubišić; Marija Kristić; Miroslav Lisjak; Katarina Mišković Špoljarić; Sonja Petrović; Sonja Vila; Andrijana Rebekić (Foods, 2022)
Fresh fruit and vegetable juices are commonly consumed as a valuable source of nutrients, while wheatgrass juice is, due to its nutritional value, used as a natural dietary supplement. The main aim of this research was to evaluate the effect of wheatgrass juice addition to apple, beet, carrot, orange, and lemon juice on total and in vitro bioaccessible concentrations of K, Ca, Mg, Mn, Fe, and Zn, vitamin C concentration, total phenolic and flavonoid content, and antioxidant activity. In comparison to other juices, wheatgrass juice had the highest total and in vitro bioaccessible concentrations of Ca, Mg, Mn, Fe, and Zn, while beet juice had the highest K concentration. Lemon and orange juices had the highest vitamin C concentration, while the highest total phenolic and flavonoid content were found in wheatgrass juice. After the addition of wheatgrass juice, Ca, Mg, Mn, and Zn concentration increased in all examined juices, vitamin C concentration increased in apple, beet, and carrot juice, total phenolic content increased in carrot juice, while total flavonoid content increased in apple, carrot, and orange juice. In comparison to the examined juices, wheatgrass juice has better nutritional value, and it could be used in a mixture with other juices to improve their nutritional value.